2014
DOI: 10.1155/2014/578342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Er:YAG Laser on Mineral Content of Sound Dentin in Primary Teeth

Abstract: The aim of the present study was to evaluate the mineral content of sound dentin in primary teeth prepared using an Er:YAG laser at two different power settings. Thirty-six primary second molars were used in this study. Three dentin slabs were obtained from each tooth, and the slabs were randomly divided into three groups: Group A, control; Group B, Er:YAG laser at 3.5 W, 175 mJ, and 20 Hz, short pulse mode; and Group C, Er:YAG laser at 4 W, 200 mJ, and 20 Hz, medium-short pulse mode. One dentin slab per group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
1
9
0
4
Order By: Relevance
“…The data from literature examined the effects of marginal percolating after cavities treated with lasers and conventional pre-treatment. Some studies reported that laser preparation resulted in an identical or even more obvious marginal percolation comparable to conventional preparation, but other studies had contradictory results [24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…The data from literature examined the effects of marginal percolating after cavities treated with lasers and conventional pre-treatment. Some studies reported that laser preparation resulted in an identical or even more obvious marginal percolation comparable to conventional preparation, but other studies had contradictory results [24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…The energy levels of laser up to 300 mJ have been reported as safe energy outputs in primary teeth. 29,30 The issue that the laser with an energy output of 400 mJ leads into melting, cracks or some areas of imperfection in dentin surfaces is a controversial issue. In a study by Zhang et al 29 some areas of melting were reported, but in some studies, no signs of cracks or carbonization have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…En consecuencia, la fuerza de unión de los sistemas adhesivos sobre las superficies de dentina puede verse afectada en la práctica clínica 19 .…”
Section: Adhesión Y Microfiltraciónunclassified
“…Por tanto, se puede decir que el uso del láser en la odontología pediátrica va desde la prevención [14][15][16][17] , operatoria 18,19 y tratamientos pulpares 10,11,15,[19][20][21][22] hasta la cirugía oral en niños 6,23 con excelentes resultados; sin embargo, aún queda mucho por estudiar y conocer.…”
unclassified